Synthesis, spectral, biological, and computational studies of template engineered macrocyclic metal complexes. Issue 19 (17th December 2022) - Kumar, Jai; Singh, Devender; Jangra, Arti; Kumar, Harish; Kumar, Parvin; Kumar, Suresh; Khanna, Radhika; Kumar, Ramesh
Abstract: A series of macrocyclic Cu 2+, Ni 2+, and Co 2+ complexes was synthesized using a template reaction between triethylenetetramine and dibenzoylmethane. These complexes may be represented by the general formula [M(C21 H26 N4 )X2 ], where M = Cu 2+, Ni 2+, and Co 2+ and X = NO3 ˉ, Clˉ, and CH3 COOˉ. Various techniques, including elemental analysis, molar conductance, magnetic moment, PXRD, thermal investigations, EPR, IR, UV-visible, and mass spectral studies, were used to characterize the synthesized complexes. Their results suggested the distorted octahedral geometry for copper complexes and octahedral geometry for nickel and cobalt complexes. All complexes showed molar conductance in the range of 8–20 ohm −1 cm 2 mol −1 that indicated the non-electrolytic nature. The DFT studies of all complexes were also performed to analyze the stability of complexes. Antibacterial activities of all complexes were also examined, and it was observed that complexes [Ni(C21 H26 N4 )(Cl)2 ] and [Co(C21 H26 N4 )(Cl)2 ] exhibited remarkable antibacterial activity. Moreover, complex [Co(C21 H26 N4 )(NO3 )2 ] showed miraculous antioxidant activity, even better than that of ascorbic acid and other complexes. The docking studies of [Ni(C21 H26 N4 )(Cl)2 ] and [Co(C21 H26 N4 )(Cl)2 ] were also performed to enforce the results obtained from the antibacterial study of these complexes. Furthermore, the drug-likeness property of all complexes was also evaluated with the help of ADMET studies. Graphical abstract: UF0001